The Development of Green Innovation: A Bibliometric Analysis - Edi Wijaya; Hendrato Nugroho (Penerbit Jurnal Indonesia, 2025)
This study conducts This study aims to (1) examine the evolution of green innovation research, (2) evaluate the objectives and key findings of recent studies, and (3) identify leading authors in the field. From an initial pool of 2,830 Scopus-indexed documents, 101 relevant articles were selected for analysis using VOSviewer software to construct bibliometric networks. The findings reveal significant growth in publications, peaking in 2022. Keyword co-occurrence analysis identified 86 items grouped into 9 distinct thematic clusters. Strong conceptual relationships were found between green innovation and environmentally friendly innovation processes, sustainability strategies, and environmental performance. The analysis highlights practical implications for reducing industrial environmental impacts, enhancing corporate competitiveness through green practices, and improving organizational reputation via sustainable development initiatives. This research provides a valuable foundation for scholars and practitioners, offering insights for future studies in green innovation and sustainable business practices.